2012
DOI: 10.1557/jmr.2012.122
|View full text |Cite
|
Sign up to set email alerts
|

Phase transformations in nanocomposite ZrAlN thin films during annealing

Abstract: Nanocomposite Zr 0.52 Al 0.48 N 1.11 thin films consisting of crystalline grains surrounded by an amorphous matrix were deposited using cathodic arc evaporation. The structure evolution after annealing of the films was studied using high-energy x-ray scattering and transmission electron microscopy. The mechanical properties were characterized by nanoindentation on as-deposited and annealed films. After annealing in temperatures of 1050-1400°C, nucleation and grain growth of cubic ZrN takes place in the film. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 53 publications
(64 reference statements)
1
11
1
Order By: Relevance
“…[1][2][3][4][5][6][7] However, additional heating, around 900 • C, will deteriorate the material properties when the AlN changes its structure from cubic to wurtzite. 8 In our previous works [9][10][11] we demonstrated that the addition of Cr into the solution leads to a formation of intermediate metastable phases of (TiCr)N and (CrAl)N where Cr dissolved in the AlN delays the onset of a detrimental cubic-to-wurtzite phase transition to higher temperatures, up to above 1000 • C. Another alloy that have shown interesting high temperature properties is (ZrAl)N. [12][13][14][15][16][17][18] Also, alloying (TiAl)N with Zr have been shown to give improved high temperature properties. [19][20][21][22] However, due to a very strong tendency towards phase separation between ZrN and AlN a process similar to what was seen in (TiCrAl)N is unlikely to play a major role in this system, instead some other decomposition trends should be expected.…”
Section: Introductionmentioning
confidence: 96%
“…[1][2][3][4][5][6][7] However, additional heating, around 900 • C, will deteriorate the material properties when the AlN changes its structure from cubic to wurtzite. 8 In our previous works [9][10][11] we demonstrated that the addition of Cr into the solution leads to a formation of intermediate metastable phases of (TiCr)N and (CrAl)N where Cr dissolved in the AlN delays the onset of a detrimental cubic-to-wurtzite phase transition to higher temperatures, up to above 1000 • C. Another alloy that have shown interesting high temperature properties is (ZrAl)N. [12][13][14][15][16][17][18] Also, alloying (TiAl)N with Zr have been shown to give improved high temperature properties. [19][20][21][22] However, due to a very strong tendency towards phase separation between ZrN and AlN a process similar to what was seen in (TiCrAl)N is unlikely to play a major role in this system, instead some other decomposition trends should be expected.…”
Section: Introductionmentioning
confidence: 96%
“…2,3 Recent efforts at improving the thermal stability of these coatings have focused on ways to stabilize the cubic MeAlN phase, for example, alloying [7][8][9][10][11][12] or multilayer structures. 3,13,14 ZrAlN, a related MeAlN, also exhibits good high temperature properties [15][16][17][18][19][20][21][22][23] and, under specific circumstances, high toughness due to a stress-induced phase transformation. 24 The ZrAlN system exhibits an even larger miscibility gap between the binary cubic phases compared to TiAlN, 25 preventing the formation of a solid solution cubic structure during growth except for low Al-contents.…”
mentioning
confidence: 99%
“…In the Zr0.50Al0.50N coating, no diffraction peaks was observed by XRD, which can be expected as ZrAlN coatings with similar composition commonly have a nanocomposite (nc) structure consisting of a mixture of small cubic and hexagonal structured grains and amorphous phases [16,22].…”
Section: Elementmentioning
confidence: 80%
“…Table II). The nanocomposite structure of the nc-Zr0.50Al0.50N coating also results in a lower hardness than that of the other coatings probably due to more pronounced grain boundary sliding [35] and perhaps even a less dense material [22]. The lowest wear rate is observed for the w- [36].…”
Section: Zone IImentioning
confidence: 95%